What is the best initial management of grade 1 or grade 2 ankle sprains?. Issue 10 (October 2017) - Farazandeh, Somayyeh; Tamura, Krystal
Abstract : EVIDENCE‐BASED ANSWER : Nonsteroidal anti‐inflammatory drugs (NSAIDs), either oral or topical, are modestly effective for decreasing pain and swelling in acute ankle sprains (SOR: A, metaanalysis of consistent RCTs). Supervised rehabilitation is slightly better than home exercises for reducing pain and improving ankle stability in the short term, but these differences disappear over time (SOR: B, systematic review of inconsistent RCTs). Current guidelines recommend NSAIDS, acetaminophen, and early mobilization as part of the initial management of ankle sprains. Evidence is insufficient regarding the value of rest, ice, compression, and elevation (RICE) (SOR: C, consensus and evidence‐based clinical guideline).